Is macular hole a risk factor for retinal detachment? - KimHyun Woong; LeeJi Eun (眼科学报, 2015)
There was an ‘outbreak’ of retinal detachment after macular hole (MH) surgery in early 2000s (1,2). Retinal detachment in a vitrectomized eye may result in a disaster of proliferative vitreoretinopathy, if the vitreous has not been removed sufficiently. The outbreak was associated with several factors in the era.